The choice of surgical treatment in patients with infected pancreonecrosis - E. A. Tseimakh; V. A. Bombizo; P. N. Buldakov; A. A. Averkina; D. N. Ustinov; A. V. Udovichenko (Вестник хирургии имени И.И. Грекова, 2018)
The objective is to study the results of different methods of surgical treatment of patients with infected pancreonecrosis and to conduct a comparative analysis of minimally invasive and traditional surgical interventions.Material and methods. The results of treatment of 206 patients with infected pancreonecrosis were analyzed. In accordance with the used method of surgical treatment, the patients were divided into 2 groups: 105 (51.0%) patients with “traditional” open interventions were included in the first group (comparison), and 101 (49.0%) patients treated with various miniinvasive technologies, or a combination of minimally invasive and “open” interventions were included in the second group.Results. It was found that the mortality rate in the second group was less than in the first group by 12.8% (p<0.05).Conclusion. Minimally invasive surgical techniques are the method of choice for delimited pancreatogenic ulcers. The use of combined surgical interventions leads to a significant reduction of postoperative mortality and duration of inpatient treatment.